The evolutionary analysis of economic policy - Wegner, Gerhard; Pelikán, Pavel (Cheltenham, UK ; Northhampton, MA, USA : Edward Elgar, 2003)
This important book analyses evolutionary approaches to economic policy. Its main purpose is to explore the policy implications of evolutionary economics, in particular of approaches inspired on the one hand by Schumpeter and revived by Nelson and Winter which deal with industrial evolution under constant institutions and, on the other hand, of approaches inspired by Hayek and North, which analyze the ways in which institutions themselves evolve.
Includes bibliographical references and index.
nmn 07/06/13
Loans
Keywords: Economic policy; Evolutionary economics